1990
DOI: 10.1007/bf00053780
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of dimethyl sulfide and dimethyl disulfide. I: Mechanism development

Abstract: Detailed theoretical (Part I, this article) and experimental (Part II) investigations are presented for the mechanism of the atmospheric photooxidation of dimethyl sulfide (CH,SCH,) and dimethyi disulfide (CH,SSCH,). In this paper, comprehensive mechanisms for the atmospheric chemistry of CH,SCH, and CH,SSCH, are developed based on fundamental considerations of all available kinetic and mechanistic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
257
2
3

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(295 citation statements)
references
References 104 publications
10
257
2
3
Order By: Relevance
“…These products are produced through reaction chains involving few branches and predominantly unidirectional radical abstraction and addition reactions (16). Given the high proportion of the ultimate sulfate product (NSS-SO 4 2− ) and the general similarity in the molecular structure of the reaction intermediates, it is inferred that the sulfur isotope composition of NSS-SO 4 2− will approximate that of oceanic DMS emissions.…”
Section: Conclusion and Implications For Marine Atmospherementioning
confidence: 99%
See 2 more Smart Citations
“…These products are produced through reaction chains involving few branches and predominantly unidirectional radical abstraction and addition reactions (16). Given the high proportion of the ultimate sulfate product (NSS-SO 4 2− ) and the general similarity in the molecular structure of the reaction intermediates, it is inferred that the sulfur isotope composition of NSS-SO 4 2− will approximate that of oceanic DMS emissions.…”
Section: Conclusion and Implications For Marine Atmospherementioning
confidence: 99%
“…This sea-to-air exchange of DMS is mediated through turbulent diffusive processes in marine environments. Once released into the atmosphere, DMS is oxidized by odd nitrogen (NOx) and odd hydrogen (HOx) species through addition and abstraction reactions (16) to form DMSO, dimethyl sulfone (DMSO 2 ), sulfur dioxide (SO 2 ), non-seasalt sulfate (NSS-SO 4 2− ), and methanesulfonic acid (MSA). These products serve as sources for sulfuric acid, which has the potential to create new aerosols that can act as cloud condensation nuclei (CCN) (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[39] Later, continuous measurements of DMS at Cape Grim demonstrated a strong seasonal cycle, with interannual variability that was matched in the sulfate aerosol. [40] The critical intermediate sulfur dioxide was hard to measure at Cape Grim, [41] but a modelling study encouraged the use of a novel technique [42] to monitor extremely low levels of sulfur dioxide, [43] showing that the most comprehensive modelling scheme for atmospheric sulfur available at the time [44,45] did an excellent job of reproducing the atmospheric sulfur cycle at Cape Grim in summer and demonstrated the influence of location (latitude), temperature, biology and photochemistry on the sulfur cycle. [43] Later work has shown that in some locations the OH radical is not the only oxidant and that halogen chemistry, in particular BrO, is probably involved in DMS oxidation.…”
Section: The Devil Is In the Detailmentioning
confidence: 99%
“…It is generally accepted that MSA is produced from the OH addition to DMS, in a mechanism highly dependent on temperature and O 2 partial pressure. On the other hand, the presence of MSIA in the atmospheric decomposition of DMS was proposed by Yin et al, 10 as a second-generation product of the DMS oxidation. However, the mechanism and the yields of MSIA formation were reasons of great discussions in the literature.…”
Section: Introductionmentioning
confidence: 98%